2022
DOI: 10.3390/ijms231911133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Pro-Excitogenic Receptor and Channel Phenotypes of the Deafferented Lumbar Motoneurons in the Early Phase after SCT in Rats

Abstract: Spasticity impacts the quality of life of patients suffering spinal cord injury and impedes the recovery of locomotion. At the cellular level, spasticity is considered to be primarily caused by the hyperexcitability of spinal α-motoneurons (MNs) within the spinal stretch reflex circuit. Here, we hypothesized that after a complete spinal cord transection in rats, fast adaptive molecular responses of lumbar MNs develop in return for the loss of inputs. We assumed that early loss of glutamatergic afferents change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…It is abundant in multiple cell populations in the spinal cord and supraspinal motor nuclei [ 16 , 17 , 18 , 19 , 20 ]. The adeno-associated viral vector (AAV) is effective in BDNF gene delivery that allows BDNF tissue levels to increase, and is beneficial for paraplegic rats with altered excitability of the MNs [ 10 , 21 , 22 , 23 , 24 ]. Our group and the Mendell group showed that after SCT, AAV-BDNF-treated rats perform alternative locomotor movements with body weight support and plantar foot placement on a moving treadmill, which was not achieved in non-treated rats [ 10 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is abundant in multiple cell populations in the spinal cord and supraspinal motor nuclei [ 16 , 17 , 18 , 19 , 20 ]. The adeno-associated viral vector (AAV) is effective in BDNF gene delivery that allows BDNF tissue levels to increase, and is beneficial for paraplegic rats with altered excitability of the MNs [ 10 , 21 , 22 , 23 , 24 ]. Our group and the Mendell group showed that after SCT, AAV-BDNF-treated rats perform alternative locomotor movements with body weight support and plantar foot placement on a moving treadmill, which was not achieved in non-treated rats [ 10 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%